Analisis Daya Saing Usahatani Kentang Dan Dampak Kebijakan Pemerintah Di Provinsi Jambi-Indonesia - Nainggolan, Saidin; Yanita, Mirawati; Yumanita, Siska (JALOW | Journal of Agribusiness and Local Wisdom, 2022)
This study aims to analyze the competitiveness of potato farming and the impact of potato farming policies. The research was conducted in Jambi Province at the production center of Kerinci Regency, by taking Kayu Aro District purposively as the research locus. Two villages were sampled, namely Batang Sa.ngir Village and Kersik Tuo Village. The sample size was determined by the Taro Yamane method and a sample of 44 farmers was obtained. Sampling method using simple random sampling. Analysis of the competitiveness and impact of government policies using the Pearson and Monke method. The results showed that potato farming has a very high competitiveness in terms of comparative and competitive advantages. This advantage is supported by the existence of a relatively high productivity, a price that benefits farmers so that private profits are greater than social benefits and the difference is very significant. The impact of the government's policy is NPCI = 0.66 < 1, meaning that the price of financial input is lower than the shadow price or the policy is protective (subsidy) on tradable inputs. NPCO = 1.13 > 1, meaning that the price of potatoes is more expensive than the shadow price or the government's policy is protective (price stability efforts) for potato commodities. EPC = 1.16 > 1 means that the government's policy on tradable inputs and commodities is able to encourage farmers to increase productivity and competitiveness.